Cardiometabolic Risk and Cognitive Decline: The Role of Socioeconomic Status in Childhood and Adulthood. (September 2019) - Oi, Katsuya; Haas, Steven
Socioeconomic conditions in childhood predict cognitive functioning in later life. It is unclear whether poor childhood socioeconomic status (SES) also predicts the acceleration of cognitive decline. One proposed pathway is via cardiometabolic risk, which has been linked to both childhood SES and earlier onset of cognitive impairment. Using data from the Health and Retirement Study, we examine the impact of childhood SES on cognitive trajectories over six years and test whether it operates through increased cardiometabolic risk and adult SES. We find that higher childhood SES leads to slower cognitive decline, partially due to lower levels of cardiometabolic risk. However, these pathways operate entirely through adult socioeconomic attainment. The results have important implications for future trends in cognitive population health within the context of growing social inequality and reduced social mobility.